2022
DOI: 10.1063/5.0078785
|View full text |Cite
|
Sign up to set email alerts
|

Environmental radiation impact on lifetimes and quasiparticle tunneling rates of fixed-frequency transmon qubits

Abstract: Quantum computing relies on the operation of qubits in an environment as free of noise as possible. Assessing the quality of this environment is a key aspect of ensuring high-fidelity implementations based on superconducting qubits. Relaxation, decoherence, dephasing, and quasiparticle tunneling rates have been measured for various shielding configurations used in the measurement environment for state-of-the-art transmon qubits. An ensemble of approximately 120 control devices was used for this study, with fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…Enhanced RF filtering along the microwave lines with Eccosorb and additional Al shielding surrounding Al 3D offset-charge transmon qubits led to a near doubling of quality factor and an increase in average quasiparticle tunneling time by two orders of magnitude [71], [287]. Measurements performed on Nb transmons showed that, while quasiparticle tunneling rates were highly sensitive to both the degree of shielding as well as the shunting capacitor size and shape, their relaxation times were not significantly impacted until the mixing chamber shield had been removed [69]. Modeling of spurious antenna modes that can be generated within transmon qubit designs at frequencies much larger than that associated with their |0⟩-|1⟩ transition have been conducted, suggesting that quasiparticle creation from radiation with these energies can produce an effective blackbody temperature of approximately 300 mK [164].…”
Section: Radiation Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced RF filtering along the microwave lines with Eccosorb and additional Al shielding surrounding Al 3D offset-charge transmon qubits led to a near doubling of quality factor and an increase in average quasiparticle tunneling time by two orders of magnitude [71], [287]. Measurements performed on Nb transmons showed that, while quasiparticle tunneling rates were highly sensitive to both the degree of shielding as well as the shunting capacitor size and shape, their relaxation times were not significantly impacted until the mixing chamber shield had been removed [69]. Modeling of spurious antenna modes that can be generated within transmon qubit designs at frequencies much larger than that associated with their |0⟩-|1⟩ transition have been conducted, suggesting that quasiparticle creation from radiation with these energies can produce an effective blackbody temperature of approximately 300 mK [164].…”
Section: Radiation Lossmentioning
confidence: 99%
“…FIG. 4: Comparison of quality factors of transmon qubits fabricated using different deposition methods and superconducting metallization: sputtered [68], [69], evaporated [70], [71] and MBE [72].…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…With the advantages of long coherence times [1][2][3][4] and simplified demands on the electronic control circuits, fixedfrequency transmon qubit [5] has been demonstrated as a leading qubit modality for quantum computing [1]. This can be partially manifested by the progress that diverse qubit architectures, which utilize fixed-frequency transmon qubits, have been demonstrated with high-fidelity gate performance, such as all-microwave controlled qubit architecture with fixed inter-qubit coupling [6][7][8][9][10][11][12][13], qubit architecture with tunable bus [14] or tunable coupler [15,16], and qubit architecture combining both fixed-frequency qubits and frequency-tunable qubits [17].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in conditions where qubit relaxations contain non-negligible contributions from quasiparticles, the variations of qubit relaxation times could also be attributed to the fluctuation in the quasiparticle density near the qubit junctions [27][28][29] or the fluctuations in quasiparticle dissipation channels [30,31]. Nevertheless, for well-shielded transmon qubit devices, transmon qubits have been shown not yet limited by losses related to quasiparticles [4]. Additionally, a recent result also suggests that quasiparticles trapped in shallow subgap states can also behave similarly to TLS [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, the hardware-platform has witnessed tremendous improvements since this initial demonstration. The size of the largest quantum processors based on this architecture now lies at 65 qubits [9], reported transmon coherence times are exceeding several hundred microseconds [27], cross-resonance gate fidelities are approaching 99.9 % with sub-100 ns gate times [28], with steady progress in holistic metrics such as quantum volume [29] as well. This raises a tantalizing question of how much these hardware improvements could extend the reach of zero-noise extrapolation to perform accurate quantum computation at a larger scale, into the realm of quantum advantage.…”
mentioning
confidence: 99%